KEBIJAKAN MONETER DAN PENGARUHNYA TERHADAP PASAR MODAL INDONESIA - Hasminidiarty Hasminidiarty (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
This research aims to test the influence of macroeconomic indicators of Indonesia, namely inflation, interest rates, exchange rates, the money supply (M2), and interest rates of deposits against the composite stock price index (JCI) at the Indonesia stock exchange. Research period used is from 1995 up to 2015. The object in this study is the composite stock price index on the Indonesia stock exchange. The data used are secondary data. Methods of data analysis used was multiple linear regression analysis with a significant level of 0.05.The results of this research show that: (a) the negative effect of inflation against the composite stock price Index (JCI) but does not have significant influence; (b) the interest rate has a positive influence against the composite stock price Index and has significant influence; (c) exchange rate against the US Dollar had a negative effect against the composite stock price Index and has a very significant influence against the composite stock price index; (d) the amount of money in circulation has a positive influence against the composite stock price Index and has a very significant influence against the composite stock price index; 1 month Deposit and have a negative effect against the composite stock price Index and has a very significant influence against the composite stock price index.Key words: inflation, interest rates, exchange rates, money supply, 1 month deposit, the composite stock price index